Orange princess has a ball - Crowne, Alyssa, 1965-; Alder, Charlotte (New York : Scholastic, 2010)
Kristina is determined to make herself a sparkly orange princess gown for the upcoming ball, but nothing seems to be going right, and Kristina's big day may just turn into a royal washout.
450
Accelerated Reader AR
Keywords: Princesses; Balls (Parties); Juvenile fiction